Northeast India : development, communalism and insurgency - Roy, Ramashray; Miri, Sujata; Goswami, Sandhya (Delhi : Anshah Pub. House, 2007)
Specially focus on Assam and Meghalaya
Includes index
Keywords: Insurgency -- India -- Meghalaya; Insurgency -- India -- Assam; Assam (India) -- Politics and government; Meghalaya (India) -- Politics and government